Celandine - Augarde, Steve (Oxford ; Corgi Books, 2005)
In Somerset, England, during World War I, Celandine becomes involved in the lives of the little people living on a hill near her family's farm, while also coming to terms with her own healing abilities and psychic gifts.
Prequel to: The Various.
Angela Misa
Keywords: Fairies -- Fiction; Self-acceptance -- Fiction; Extrasensory perception -- Fiction; Farm life -- Fiction; Somerset (England) -- Fiction; Great Britain -- History -- George V, 1910-1936 -- Fiction